2017
DOI: 10.1097/iop.0000000000000824
|View full text |Cite
|
Sign up to set email alerts
|

Porous Versus Nonporous Orbital Implants After Enucleation for Uveal Melanoma: A Randomized Study

Abstract: Patient-reported outcomes after enucleation for uveal melanoma indicate no major differences between hydroxyapatite and acrylic implants in surgical outcomes and patient satisfaction. There was a higher prevalence of ptosis with AC and a greater need of ocularists' visits with HA at around 6 months observed by ocularists.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 18 publications
0
13
0
Order By: Relevance
“…Studies comparing the use of nonporous and porous implants on adult populations have found that complication rates are low and comparable, with acrylic implants possibly providing better prosthetic movement. 11,12 A recent study by Mourits, et al 20 directly comparing porous and nonporous implants in retinoblastoma patients found that the use of HA led to more exposures (12.7%) than nonporous acrylic implants (4.9%), although the difference was not statistically significant. 20 In non-comparison studies, the rates of complications with porous implants are generally higher than with nonporous implants.…”
Section: Discussionmentioning
confidence: 99%
“…Studies comparing the use of nonporous and porous implants on adult populations have found that complication rates are low and comparable, with acrylic implants possibly providing better prosthetic movement. 11,12 A recent study by Mourits, et al 20 directly comparing porous and nonporous implants in retinoblastoma patients found that the use of HA led to more exposures (12.7%) than nonporous acrylic implants (4.9%), although the difference was not statistically significant. 20 In non-comparison studies, the rates of complications with porous implants are generally higher than with nonporous implants.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, treatment differences are probably attributable to pre-treatment differences between treatment groups, and unlikely to be a consequence of enucleation. The equivalence of appearance concerns between enucleation and PBR may reflect either recent advances in the development of implants and prostheses [14,26] or a generally low concern about appearance in our sample of older patients [25].…”
Section: Discussionmentioning
confidence: 93%
“…The cost difference itself may be prohibitive to convince the patient for surgery. [ 26 ] This leaves us with the option of DFG. However, the requirement for a second site incision and the higher rate of graft necrosis in repeat socket surgeries makes this procedure an unattractive choice.…”
Section: Discussionmentioning
confidence: 99%